Perbandingan Persentase Brondol di Berbagai Macam Areal di Perkebunan Kelapa Sawit - Ramadhan, M.Fauzan; Gunawan, Sri; Tarmadja, Samsuri (AGROISTA : Jurnal Agroteknologi, 2024)
Palm oil productivity is influenced by many factors. One factor is crop rotation. Harvest rotation greatly influences productivity in oil palm plantations. Obstructed harvest rotation causes the number of fruit bunches to increase in an area compared to the weight of fresh fruit bunches (FFB) harvested. The percentage of brondol in oil palm plantations is very important because it will affect the average bushel weight (BJR) and payments to employees for oil palm plantation companies. The decrease in BJR due to the high percentage of brondol will also have an impact on the morale of workers, especially harvesters on oil palm plantations because the harvest base will be higher to get a harvest premium. This research aims to determine the comparison of the percentage of brondol in various areas, namely hilly, lowland and plain areas and to find out the causes of the high percentage of brondol in the treatment blocks. This research uses an agronomic trait survey method by observing secondary data on productivity and percentage of brondol in the last six years, then analyzed using the t test at a level of 5%.  This research was carried out at PT. Cahaya Nusa Gemilang (CNG) Kenanga Estate garden, Marau District, Ketapang Regency, West Kalimantan. The results of the analysis show that plain areas have the best productivity and percentage of brondol compared to lowland and hilly areas.